FRI0504 Reliability and Validity of Patients Reported Outcomes in Poly/Dermatomyositis: A Pilot Study Using an Italian Version of Myositis Activity Profile (MAP) in A Monocentric Cohort of Patients. (10th June 2014) - Barsotti, S.; Neri, R.; Ferrari, C.; Talarico, R.; Tripoli, A.; Iacopetti, V.; d'Ascanio, A.; Bombardieri, S.
Abstract : Background: the evaluation of disease activity in patients with polymyositis (PM) and dermatomyositis (DM) still represents a challenge. International Myositis Assessment & Clinical Studies Group (IMACS) has performed a consensus on a Core Set Domains for the assessment of disease activity in PM/DM; moreover, no disease-specific patient reported outcome (PRO) questionnaire has been proposed for adults. The first disease specific activity limitations questionnaire is represented by the myositis activity profile (MAP), that was first developed in Sweden and then validated and tested in US patients in 2012. Objectives: To evaluate measurement properties of MAP in adult patients with PM/DM in a monocentric cohort of Italian patients. Methods: The study enrolled a cohort of consecutive PM/DM patients referred to our unit who have performed an Italian version of the MAP questionnaire. At time of the evaluation, the following measures included in the IMACS core set were performed: manual muscle test 8 (MMT8), Health Assessment Questionnaire (HAQ), disease effect on well-being on a visual analogic scale (VAS) and physician assessment of disease activity by VAS; moreover, determination of serum creatine kinase (CK) levels was performed. Statistical analysis was performed using Pearson's correlation. High correlation is defined for Pearson's r coefficient between -0.5 to -1.0 (negative correlation) or 0.5 to 1 (positive correlation); medium correlation between -0.3 to -0.5 (or 0.3 to 0.5); Low correlation between -0.1 to -0.3 (or -0.1 to -0.3). Results: Twenty nine (12 DM, 17 PM; M/F=10/19; mean ± SD age: 57.3±12 years; mean ± SD disease duration: 8.9 years ±6.9) patients with a diagnosis of PM/DM according to Bohan and Peter's criteria completed the MAP questionnaire. mean ± SD CK level resulted of 337±604 (UI/ml). Mean ± SD MMT8 values was 70.3±10 and mean ± SD HAQ 0.76 (±0.77); moreover, mean ± SD patient's VAS was 4.14 cm ±2.7, while mean ± SD physician VAS 3.31±2.3. Table 1 summarized the Pearson's r coefficient of the regression. A significant correlation was found between MMT8 and the movement subscales of MAP and between HAQ and all the MAP subscales. No correlation was found between CK levels and MAP subscales. Six out of 29 of the cohort (20%) reported a score 0 (no limitation) on the HAQ, while only 11% reported a score 1 (no limitation) in all subscales and single items of the MAP. Conclusions: Although further data are necessary to confirm this hypothesis, this explorative study suggest that MAP could represent a useful tool to assess disease activity in PM/DM patients. Although HAQ and MAP show significant correlations, MAP seems to be more sensitive to detect activity limitations in patients with PM/DM. Since MAP is not time consuming and is easily to administer, is desirable that a validation of the Italian version is needed to establish sensitivity to change, reproducibility and reliability of the test in PM/DM patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5451